Hidróxido de cálcio associado ao paranoclorofenol canforado e à clorexidina como curativo de demora com plug apical de MTA em reimplante dentário tardio - Almeida, Melyna Marques de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
After dental avulsion the disruption of neurovascular bundle occurs and especially in cases of delayed replantation the possibility of revascularization is remote, leading to pulp necrosis. Some drugs have been studied as intracanal dressing aiming to prevent and / or treat the root resorption, among them, the calcium hydroxide [Ca (OH) 2]. The aim of this work is to analyze the effect of Ca (OH)2 paste associated with propylene glycol, paramonochlorophenol (PMCC) and 2% chlorhexidine (CHX) solution as intracanal dressing after placing an MTA apical plug in delayed replantation of rat teeth. Thirty rat had the right upper incisor extracted and left on the bench for an hour. Then the dental papilla, the enamel organ, the pulp and the periodontal ligament were removed. Then the teeth were immersed in a 2% solution of sodium fluoride acidulated phosphate for 10 minutes. After this procedure, the root canals were dried with absorbent paper cones and the teeth were divided into three experimental groups according to the type of intracanal dressing: Group I: canals filled with Ca (OH)2 paste and propylene glycol, Group II: filled with Ca (OH)2 and PMCC and Group III filled with Ca (OH)2 and 2% CHX. After placing the dressing an MTA apical plug was implemented. The alveoli were irrigated with saline solution and teeth were replanted. In group I, compared to group II and III, root resorption was greater in extent and depth, presenting acute inflammatory infiltrate in some areas, featuring an inflammatory root resorption. In the apical region, bone neoformation ocurred and the connective tissue in contact with MTA showed few chronic inflammatory cells. The Ca(OH)2 with the PMCC and CLX association could be a dressing option for delayed tooth replantation and the MTA apical plug leads to the repair, specially for teeth with incomplete root formation, keeping the efficiency and limiting the dressing intracanal action on the root canal

Após a avulsão dentária ocorre o rompimento do feixe vásculo-nervoso, e especialmente nos casos de reimplante tardio a possibilidade de revascularização é remota levando à necrose pulpar. Alguns medicamentos têm sido estudados como curativo intracanal com o objetivo de prevenir e/ou tratar a reabsorção radicular e dentre eles, o hidróxido de cálcio [Ca(OH)2]. O objetivo deste trabalho é analisar o efeito da pasta de Ca(OH)2 associada ao propileno glicol, ao Paramonoclorofenol (PMCC) e à solução de Clorexidina a 2% (CHX) como curativo intracanal após a colocação de um plug apical de MTA no reimplante tardio de dentes de rato. Trinta ratos tiveram o incisivo superior direito extraído e deixado em bancada por uma hora. Em seguida foi removida a papila dentária, o órgão do esmalte, a polpa e o ligamento periodontal. Em seguida os dentes foram imersos em solução de fluoreto de sódio fosfato acidulado a 2% por 10 minutos. Após esse procedimento os canais radiculares foram secos com cones de papel absorventes e os dentes divididos em três grupos experimentais de acordo com o curativo de demora: Group I: canais preenchidos com pasta de Ca(OH)2 e propileno glicol, Group II: com Ca(OH)2 e CMCP e Group III: com Ca(OH)2 e CHX 2%. Após a colocação do curativo foi realizado um plug apical de MTA. Os alvéolos foram irrigados com soro fisiológico e os dentes reimplantados. No grupo I quando comparado ao grupo II e III a reabsorção radicular foi maior em extensão e profundidade com presença de infiltrado inflamatório agudo em algumas áreas caracterizando uma reabsorção inflamatória. Na região apical houve neoformação óssea e o tecido conjuntivo em contato com o MTA apresentava poucas células inflamatórias crônicas. A associação do Ca(OH)2 com o PMCC e a CLX podem...
Keywords: Reimplante dentário; Hidróxido de cálcio; Clorexidina; Tooth replantation